Kedudukan dan peranan raja-raja dalam pentadbiran agama Islam - Mohd Kamal, Mohd Hisham (Dewan Bahasa dan Pustaka, 2007)
This work discusses the position and the role of Malay Rulers as Heads of the religion of Islam in their respective States in the administration of Islam.